“Ethics are generally not in play here”: The neutralization techniques of “the bad boy of pharma” Martin Shkreli - Gustav Grut (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In 2015, the American company Turing Pharmaceuticals increased the price of the drug Daraprim by 5,000 percent overnight. Politicians and healthcare representatives accused Turing’s CEO, Martin Shkreli, of having harmed both vulnerable patient groups and the healthcare system. The present article aims to attain an understanding of how Shkreli justified increasing the price and restricting the distribution of the drug Daraprim. Statements made by Shkreli in four video interviews were analyzed on the basis of Sykes and Matza’s (1957) theoretical framework of neutralization techniques. All techniques of neutralization were identified. Shkreli shifted the blame to other actors, denied the existence of victims and of harm to the nation’s healthcare system, characterized his accusers as corrupt, and portrayed profit maximization as a more important goal than public health.